2009
DOI: 10.1016/j.jmb.2009.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pseudorepeat Rearrangement on α-Synuclein Misfolding, Vesicle Binding, and Micelle Binding

Abstract: The pathological and physiological hallmarks of the protein α-synuclein are its misfolding into cytotoxic aggregates and its binding to synaptic vesicles, respectively. Both events are mediated by seven 11-residue amphiphilic pseudorepeats and, most generally, involve a transition from intrinsically unstructured to structured conformations. Based upon α-synuclein interactions with aggregation-inhibiting small molecules, a α-synuclein variant termed SaS, wherein the first six pseudorepeats had been rearranged, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 75 publications
(151 reference statements)
11
77
0
Order By: Relevance
“…Using a variety of techniques including fluorescence correlation spectroscopy (FCS) and CD spectroscopy, it has been shown that PE enhances α-syn membrane interaction [90] and that α-syn favors PA and PI over PS and PG [9094]. In addition to vesicles containing anionic lipids, α-syn also can bind to lipid droplets [96] and SDS micelles [26, 9799]. …”
Section: α-Synuclein Interacts With Model Membranesmentioning
confidence: 99%
“…Using a variety of techniques including fluorescence correlation spectroscopy (FCS) and CD spectroscopy, it has been shown that PE enhances α-syn membrane interaction [90] and that α-syn favors PA and PI over PS and PG [9094]. In addition to vesicles containing anionic lipids, α-syn also can bind to lipid droplets [96] and SDS micelles [26, 9799]. …”
Section: α-Synuclein Interacts With Model Membranesmentioning
confidence: 99%
“…50 The weighted average of the 1 H and 15 N chemical shift difference (Δδ ave = (0.5[Δδ( 1 H) 2 + (0.2Δδ ( 15 N)) 2 ])1/2) and the ratio of peak intensities between the different experiments were derived and presented by using the software Grace (plasma-gate.weizmann.ac.il/Grace), together with the previously reported 1 H and 15 N chemical shift assignment for α-Syn. 51,52 ThT binding assay…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The greater density of β-branched residues in the adjacent sixth and seventh repeats is particularly important for fibril formation 24,25 . In studies of constructs with reordered repeats, it was observed that when the sixth and seventh repeats are separated by the insertion of other repeats mature fibril formation did not occur and β-structure formation was inhibited.…”
mentioning
confidence: 99%